Penggunaan Syair Arab Pra-Islam dalam Tafsir Alquran: Kajian Hermeneutik terhadap Pemikiran Thaha Husain - Sufriyansyah, Sufriyansyah; Arifinsyah, Arifinsyah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This paper aims to elucidate Thaha Husain's thoughts on the use of pre-Islamic poetry in the exegesis of the Quran. Husain was a contemporary Islamic thinker who emphasized the importance of Islamic reasoning in the effort to reconstruct a comprehensive understanding of the Quranic text. The focus of the study primarily addresses the authenticity of pre-Islamic poetry, its urgency in interpreting the Quran, and how the Quran views pre-Islamic Arab society. Husain perceives that Quranic teachings align with rational thought. He endeavors to reconstruct Islamic thought through hermeneutical and critical-historical approaches, particularly through literary and historical lenses. This research indicates that much of the pre-Islamic poetry was not composed during the pre-Islamic era by pre-Islamic Arab poets but by imitators during the Abbasid Dynasty for various purposes: political, religious, storytelling, and hadith narrators. According to Thaha Husain, many pre-Islamic poems do not resonate with pre-Islamic Arabs or objectively depict pre-Islamic Arab society. Husain employs Western scientific concepts such as semiology, philology, and Cartesian deconstruction as analytical tools in examining the Quran. It is not surprising that Husain's skepticism in evaluating pre-Islamic Arab literature has stirred controversy in Egypt.